PENGARUH TAX AMNESTY DAN PENGETAHUAN PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI (Studi Kasus di KPP Pratama Wonocolo Surabaya) - William Thomas; Dedhy Sulistiawan (CALYPTRA, 2018)
Tax is one of the most important aspects of its role as a source of state revenue, therefore the country's largest income comes from the tax sector. Taxpayer compliance becomes one of the parts that should be improved. Tax amnesty and tax knowledge can be a problem-solving low tax compliance level. The purpose of this study is to determine and analyze the effect of tax amnesty and tax knowledge on taxpayer compliance in KPP Pratama Wonocolo Surabaya. Sampling technique in this study using unknown population that is as much as 72 people. The analytical method used in this study is multiple linear regression analysis, classical assumption test, validity test, reliability test, f test, t test, multiple correlation coefficient (R) and determination coefficient (R2). The results showed that tax amnesty and knowledge of taxation have a significant effect on taxpayer compliance in KPP Pratama Wonocolo Surabaya. The result of t test on tax amnesty is 5,177 with significance value equal to 0,000 (<0,05) so that H1 is accepted. Tax amnesty has a significant positive effect on taxpayer compliance. The result of the t test of tax knowledge is 2,605 with the significance value of 0,011 (<0,05) so that H2 is accepted. Tax knowledge has a significant positive effect on taxpayer compliance. F test results of 0.000 which means significance less than 0.05. So it can be concluded that tax amnesty and knowledge taxation simultaneously have a significant influence on taxpayer compliance so that hypothesis H3 proved true.